IMPACT OF EDUCATION AND SPIRITUAL MESSAGE ON SELF EVALUATION AND CONSCIOUSNESS DEVELOPMENT OF MOTHERS OF CHILDREN WITH CEREBRAL PALSY - Senad Mehmedinović; Edina Šarić (Human Research in Rehabilitation, 2015)
The aim of the research was to determine the impact of education and spiritual message on self-evaluation and consciousness development of mothers of children with cerebral palsy. Research included the sample of 30 respondents. After evaluation of the initial status, 7 mothers gave up, so in the end, total sample was consisted of 23 respondents. Research was conducted by specially conceived protocols. Educations, and one modification of psychophysical relaxation based on Jacobson concept, were used. Multidimensional approach in inducing personal states of consciousness of the respondents, with specifically harmonically background of learning and listening to spiritual messages was used during the psychophysical relaxation. In order to review the research objective that was set, two modified scales of self-evaluation of mother herself and of the child. In order to check the hypothesis of the research, t-test for dependent sample of the respondents, was used. Based on the analysis of the obtained results, we could conclude that it has come to significant changes in applied sample of the respondents, during the séances, and that changes manifested in the levels of self-evaluation for controlled variables, of how mothers perceived themselves and their children, stimulated by spiritual messages during the séances.